Who will care for me? : a qualitative research on the practice of filial piety among the Malays in contemporary Singapore. - Nurlizawaty Jalil. (2010)
Since its legislation in 1996, the “Maintenance of Parent Act” has received considerable attention with regard to the debate on filial obligation. With Singapore’s aging population, a decline in the informal support of the elderly is feared. The paper takes a fresh perspective of the traditional idea of filial piety and analyzes its practices among the Malays in Singapore. Referring to Max Weber’s theoretical work on rationalization, it seeks to demonstrate how modernization has displaced traditional values to other formal values. Also using Marcel Mauss’s classical work called “The Gift”, the results of the study discusses some emerging themes evolving around forms of reciprocity, changing structure of authority and the gendered dimension of filial piety. The findings conclude how family relations are reduced to exchange value and that there is still a dynamic sexual division of labour in elderly care despite the decline of the traditional social order in Singapore.